Síntese, caracterização e estudo termoanalítico dos isoftalatos de lantânio (III), cério (III), praseodímio (III), neodímio (III), samário (III), európio (III) e gadolínio (III) - Nunes, Wilhan Donizete Gonçalves (2015)
In the last years the interest in the chemistry of coordination compounds of polycarboxylic acids and lanthanides or transition metals has substantially increased, due to their interesting characteristics, such as gas storage (Metal-organic frameworks compounds), luminescence and magnetic properties. A literature survey reveals few studies investigating the properties of lighter lanthanide coordination compounds obtained by soft chemistry routes, and mainly the study of their thermal properties in air atmosphere. In this work the reaction between sodium isophthalate and lighter lanthanides solutions (La – Gd) except Pm, led to the formation of two new coordination compounds, and five already reported in the literature, whose thermal behavior and infrared spectra was investigated. The compounds was characterized by simultaneous Thermogravimetric and differential scanning calorimetry analysis (TG-DSC), differential scanning calorimetry (DSC), Fourier Transform Infrared Spectroscopy (FTIR), thermogravimetric analyses coupled to Fourier Transform Infrared spectroscopy (TG-FTIR) and EDTA complexometry. With the TG-DSC and TG-FTIR data was possible to determinate the general formula of compounds (Ln2(L)3.nH2O, where Ln = La – Gd, except Pm, L = isophthalate, n varies from 2 to 13,5), thermal stability and molar dehydration enthalpy per water molecule, as well as the main evolved gases during thermal decomposition (H2O, CO2 and CO). The FTIR spectra suggest that metal-ligand coordination occurs in the bridging bidentate mode.